Kepemimpinan dalam Pendidikan Kristen untuk Pendewasaan Warga Gereja Kemah Injil (Kingmi) di Tanah Papua - Asso, Ardi; Pigai, Fredi; Watipo, Arson (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
This research aims to analyze the function of leadership in Christian education for the maturation of Kemah Injil Church (KINGMI) congregations in Tanah Papua. This research uses a quantitative method with a descriptive correlational approach. Data were collected through interviews and questionnaires. The results revealed that the tendency of pastors to be active educational leaders has a